2017
DOI: 10.1080/14992027.2017.1366671
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of mothers regarding infant hearing loss in Changsha, Hunan province, China

Abstract: Mothers were concerned about baby's hearing and the attitude was positive. However, the correct recognition rate towards some risk factors for HL was low. Action needs to be taken to raise awareness about ear and hearing care, prevent HL caused by preventable causes and prompt early identification, early diagnosis and intervention of HL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
11
7
1
Order By: Relevance
“…However, the results revealed poor knowledge regarding jaundice, measles, and convulsion as risks for HL. 99% of participants reported that they would screen their babies after birth if the service was available [12]. Another study examined 100 mothers and 50 fathers, who completed a questionnaire in in-person interviews.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results revealed poor knowledge regarding jaundice, measles, and convulsion as risks for HL. 99% of participants reported that they would screen their babies after birth if the service was available [12]. Another study examined 100 mothers and 50 fathers, who completed a questionnaire in in-person interviews.…”
Section: Introductionmentioning
confidence: 99%
“…In order to optimise the success of the evolving audiology service, the present study was conducted to investigate parental knowledge and attitudes towards childhood hearing loss and hearing services. The study differs from the previous literature (Olusanya, Luxon, et al, 2006b;Swanepoel & Almec, 2008;Wang et al, 2017) by 1…”
Section: Introductioncontrasting
confidence: 80%
“…Similar results were reported in the Indian study by Rajagopalan and colleagues (2014), however, another study from India as well as the studies from China, Nigeria and South Africa, showed better scores for both jaundice (20-47%) and delayed cry at birth (29.7-66%) (Olusanya, Luxon, et al, 2006b;Swanepoel & Almec, 2008;Wang et al, 2017). This presents an opportunity to reinforce maternal and neonatal health care messages during hearing promotion activities.…”
Section: Attitudes To Paediatric Audiology Servicessupporting
confidence: 74%
See 2 more Smart Citations